2019
DOI: 10.1063/1.5086327
|View full text |Cite
|
Sign up to set email alerts
|

Rotating electroosmotic flow through a polyelectrolyte-grafted microchannel: An analytical solution

Abstract: We investigate the flow dynamics of an incompressible fluid in a polyelectrolyte grafted rotating narrow fluidic channel under the influence of an externally applied electric field. Here, we invoke an analytical formalism to solve the transport equations governing the flow dynamics in the rotating environment. We bring out the rotational force driven complex flow dynamics in the channel as modulated by the soft layer induced alteration in the electrostatic potential under electrokinetic actuation. We observe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…This consideration allows us to consider one-dimensional flow analysis by ignoring the sidewall effect. 7,30 Moreover, we consider that the channel is rotating about the z -axis at a constant angular velocity Ω. In this study, we assume that the nanoparticles are in thermal equilibrium with the base fluid, while the interfacial slip is ignored between the particle and fluid.…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…This consideration allows us to consider one-dimensional flow analysis by ignoring the sidewall effect. 7,30 Moreover, we consider that the channel is rotating about the z -axis at a constant angular velocity Ω. In this study, we assume that the nanoparticles are in thermal equilibrium with the base fluid, while the interfacial slip is ignored between the particle and fluid.…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…1,2 Because of the numerous applications of microflow in a rotating channel, many researchers have investigated several aspects of the underlying transport features of rotational microfluidics considering both the Newtonian and non-Newtonian fluids in recent years. [3][4][5][6][7] Although the flow of nanofluids in a rotating microfluidic platform is of vital importance for several reasons, the underlying effect is not well explored to date. We would like to mention here a few important motivating factors for the present analysis: first, to explore the physics involved with the flow dynamics of nanofluids in a rotating narrow fluidic pathway under influence of electro-magnetic forcing, while the second one is essentially from the perspective of its huge applications, typically in controlling the microflows, micro-mixing, reduction in clogging and essentially for system miniaturization.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of lateral confinement was discussed in detail for Newtonian fluid by Ng and Qi [20] , power law fluid by Kaushik et al [21] and viscoelastic fluid by Kaushik et al [22]; the authors found recirculation loops using streamlines which showed the importance of rotational flow as a method of inducing mixing withing the fluid. In more recent studies the effect of PE layer grafting on rotational EOF of Newtonian fluid for different charge distributions were studied by Kaushik et al [23] and Liu and Jian [24]. Kaushik et al [23] found a significant enhancment in the flow velocities with increasing the size of the PE grafted layer in line with the net throughput increase due to the presence of PE grafted layer as reported by Gaikwad et al [10].…”
Section: Introductionmentioning
confidence: 83%
“…Microflows are commonly known as the low Reynolds number flows and hence, always fall in the laminar regime of classical fluid dynamics [3,12,[18][19][20][21]. It may be mentioned here that owing to the low Reynolds number (Re << 1), the nonlinear convective effects are often neglected while analyzing the dynamical behavior of underlying transport in narrow fluidic pathways having different geometrical configurations [22][23][24].…”
Section: Introductionmentioning
confidence: 99%